2019
DOI: 10.3390/en13010019
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adsorption Cycle for High-Efficiency Adsorption Heat Pumps and Chillers: Modeling and Simulation Results

Abstract: A novel thermodynamic cycle for adsorption heat pumps and chillers is presented. It shows a significant improvement of the internal heat recovery between the adsorption and the desorption half cycle. A stratified thermal storage, which allows for a temperature-based extraction and insertion of storage fluid, is hydraulically coupled with a single adsorber. The benefit is an increased efficiency by reusing the released heat of adsorption for regeneration of the adsorber and by rendering possible low driving tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Schamberger et al [2] comprehensively described and analyzed a new Stratisorp cycle, which is an advanced version of the common adsorptive cycles with internal heat recovery [3]. The basic concept of the Stratisorp cycle is the connection of the adsorber with a well-insulated, stratified thermal storage tank, where the heat released during the adsorption phase is stored.…”
Section: Development Of Novel and Optimization Of Known Ahts Applicat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Schamberger et al [2] comprehensively described and analyzed a new Stratisorp cycle, which is an advanced version of the common adsorptive cycles with internal heat recovery [3]. The basic concept of the Stratisorp cycle is the connection of the adsorber with a well-insulated, stratified thermal storage tank, where the heat released during the adsorption phase is stored.…”
Section: Development Of Novel and Optimization Of Known Ahts Applicat...mentioning
confidence: 99%
“…However, it is reached at the expense of new irreversibility, due to convective mixing within the storage tank. Yet, the total entropy generation is reduced (see Figure 6 in [2]), thanks to the internal heat recovery in the storage tank.…”
Section: Development Of Novel and Optimization Of Known Ahts Applicat...mentioning
confidence: 99%
“…It is worth noticing that in most cases of adsorption chillers, the medium that heats or preheats the bed is water and, in some cases, also thermal oil [34,35]. Ng et al [36] suggested that adsorption chillers can be driven by low-temperature steam, but they did not provide any information about the effects of using steam for bed regeneration on the operating parameters, e.g., temperatures, pressures and COP, of the chiller.…”
Section: Desalination Technology Electrical Energymentioning
confidence: 99%
“…The mass and heat transfer were also interpreted using this model. They quantitatively studied the regeneration temperature on the cooling performance [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%